FgRad50 Regulates Fungal Development, Pathogenicity, Cell Wall Integrity and the DNA Damage Response in Fusarium graminearum - Zhang, Chengqi; Ren, Xuexiang; Wang, Xintong; Wan, Qiong; Ding, Kejian; Chen, Li (Frontiers in Microbiology, 2020)
Rad50 is a member of the double strand break repair epistasis group of proteins that play important roles in regulating DNA damage checkpoint signalling, telomere maintenance, homologous recombination and non-homologous end-joining in eukaryotes. However, the function of Rad50 in fungal plant pathogens remains unknown. In this study, we report the functional investigation of FgRad50 in the wheat head blight pathogen Fusarium graminearum. FgRad50 is an orthologue of Saccharomyces cerevisiae Rad50 that could restore the sensitivity of the yeast Rad50 mutant to DNA damage agents. The FgRad50 deletion mutant (ΔFgRad50) exhibited defective vegetative growth, asexual/sexual development and virulence, as well as disrupted deoxynivalenol biosynthesis. Moreover, deletion of FgRad50 resulted in hypersensitivity to DNA damage agents. Unexpectedly, FgRad50 plays a key role in responses to cell wall-damaging agents by negatively regulating phosphorylation of FgMgv1, a MAP kinase in the cell wall integrity pathway. Taken together, these results suggest that FgRad50 plays critical roles in fungal development, virulence and secondary metabolism in F. graminearum, as well as cell wall integrity and the DNA damage response.